The relationship between interpersonal communication competence, intercultural communication competence and heart rate variability among international postgraduate students - Abdul Qahar, Sarwari (2017)
Previous studies on interpersonal communication competence and intercultural communication competence were mostly conducted in the western parts of the world. The findings from such work were reported based on the answers of individuals on survey questionnaires. It is arguable that whether the results from studies in the western parts of the world answer the probable questions for the Asian context of communication, and whether the results from the regular surveys are relevant enough. Thus, this study was carried out to assess the relationship between interpersonal communication competence (IPCC), intercultural communication competence (ICCC), and heart rate variability (HRV) among international postgraduate students of a Malaysian public University. An embedded design of mixed methods which included quantitative, interview and HRV data sets was applied to conduct this study. The participants of this study were 128 postgraduate students from 17 different countries. The results from this study have confirmed the existence of relationships between IPCC, ICCC and HRV attributes of the participants. The results have also confirmed that the participants who were good in HRV were also good in IPCC and ICCC, and vice versa. The mean scores of individuals with good HRV scores and relatively low HRV scores, for IPCC and ICCC were 171.7 and 164.9 respectively. Based on the results, the participants with higher mean scores in IPCC had desirable scores in HRV as well. The participants with higher scores in IPCC with scores of 22.6 in the first relaxation session and 17.6 in the mental arithmetic test, while the participants with relatively low scores in IPCC got 7.5 and 12.1 for the mentioned sessions of HRV, respectively. The findings from this study confirmed the relationship between interpersonal communication competence and HRV of the participants. However, the mean score of the participants for IPCC (99.46) was higher than their mean score for ICCC (67.57). It means that in some cases individuals might be good in interpersonal communication because of their contacts with their own people, but they are still not good in intercultural communication because of the lack of their interactions with other international postgraduate students. Based on the results, it was found that their personal abilities, positive attitudes towards cultural differences, their good levels of English language proficiency, and the available environmental opportunities helped most of the participants to have more successful interactions.